2014
DOI: 10.4049/jimmunol.1301234
|View full text |Cite
|
Sign up to set email alerts
|

The Very Low Density Lipoprotein Receptor Attenuates House Dust Mite–Induced Airway Inflammation by Suppressing Dendritic Cell–Mediated Adaptive Immune Responses

Abstract: The very low density lipoprotein receptor (VLDLR) is a member of the low density lipoprotein receptor family that binds multiple ligands and plays a key role in brain development. Although the VLDLR mediates pleiotropic biological processes, only a limited amount of information is available regarding its role in adaptive immunity. Here, we identify an important role for the VLDLR in attenuating house dust mite (HDM)-induced airway inflammation in experimental murine asthma. We show that HDM-challenged Vldlr−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Single cell suspensions of mediastinal lymph nodes (MLNs) from either saline- or HDM-challenged mice were prepared by filtering through a 100 μm-cell strainer, as previously described [22]. After red blood cells were lysed with Red Blood Cell Lysing Buffer (Sigma-Aldrich), MLN cells were re-suspended in RPMI-1640 medium supplemented with 10% fetal bovine serum, 2 mM L-glutamine, 100 IU/mL penicillin, 100 μg/mL streptomycin, 250 ng/mL amphotericin B and 3.5 μL/L 2-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Single cell suspensions of mediastinal lymph nodes (MLNs) from either saline- or HDM-challenged mice were prepared by filtering through a 100 μm-cell strainer, as previously described [22]. After red blood cells were lysed with Red Blood Cell Lysing Buffer (Sigma-Aldrich), MLN cells were re-suspended in RPMI-1640 medium supplemented with 10% fetal bovine serum, 2 mM L-glutamine, 100 IU/mL penicillin, 100 μg/mL streptomycin, 250 ng/mL amphotericin B and 3.5 μL/L 2-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…This is a schematic of molecular interactions between the master regulators of the cilium assembly module. Functional activity and relationships based on prior literature (solid arrows) [45][46][47][48][49][55][56][57][58][59] and novel interactions identified by this study's probabilistic causal gene network (dashed arrows) are shown. FOXJ1 (shown in red) was a master regulator gene in the ARIA-1 cohort of children with severe persistent asthma and the ATOM cohort of adults with mild/moderate asthma.…”
Section: Results From the Atom Study An Independent Cohort Of Subjectmentioning
confidence: 99%
“…However, it could not be concluded that increased VLDLR in protein deficiency affected inflammation because plasma ALT concentration or expression of inflammatory marker genes in the liver was not affected by Vldlr deficiency. In addition, many studies have reported that VLDLR promotes inflammation, and few suppress it 36 . Further studies are required to clarify the role of VLDLR in the liver under protein-restriction.…”
Section: Discussionmentioning
confidence: 99%